Loss Analysis and Calculation for Three-level IGBT Inverter - ZHU Wu; XIN Li; LI Yanyong; ZHANG Donghui (Kongzhi Yu Xinxi Jishu)
Taking three-level converter application as an example, this paper analysed the components and influence factors of heat loss of working IGBT, presented an approach to calculate the heat loss of IGBT in three-level converter by different control methods, used the simulation or testing data as input to obtain heat losses of each IGBT in a three-level topology converter, and obtained a result whose error is within 2%. Furthermore, this approach can also be applied to the product design on early stage for precise computation of heat losses. With this approach, it is more likely to choose a reasonable cooling system which can guarantee that junction temperature is below permitted values and a rational redundant capacity of cooling system at the same time. Precise calculation of heat losses of the system with other power devices may refer to this paper as well.